Interactive Mobile Applications for Social Communication in Deaf and Hearing-Impaired Populations: A Systematic Review - Asma Syafira; Yuana, Rosihan Ari (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Mobile applications have become an important tool in reducing communication barriers for individuals with hearing impairments. While sign language enables communication within the deaf community, challenges remain when interacting with hearing individuals who do not understand sign language. This study aims to identify types of mobile applications developed for this purpose, analyze how their features support communication skills, and evaluate their impact on social interaction. Using a systematic literature review (SLR) with the PRISMA approach, 21 articles indexed in Scopus and DOAJ were analyzed. The findings reveal diverse applications, including AI-based sign language translators, interpreter-assisted communication tools, deaf-friendly social media, gesture recognition, 3D sign language animation, and real-time speech-to-text. Key features such as real-time translation, interactive tutorials, and 3D animations enhance sign language learning, promote independence, and increase social participation. Mobile applications demonstrate significant positive impacts on accessibility, education, healthcare, and daily interactions, while fostering inclusion and empowerment for deaf individuals. This study also introduces the inclusive mobile communication framework, which integrates technological affordances with the mobile learning principles, universal design for learning, and the social model of disability.